2017
DOI: 10.1371/journal.ppat.1006538
|View full text |Cite
|
Sign up to set email alerts
|

A SIV molecular clone that targets the CNS and induces neuroAIDS in rhesus macaques

Abstract: Despite effective control of plasma viremia with the use of combination antiretroviral therapies (cART), minor cognitive and motor disorders (MCMD) persist as a significant clinical problem in HIV-infected patients. Non-human primate models are therefore required to study mechanisms of disease progression in the central nervous system (CNS). We isolated a strain of simian immunodeficiency virus (SIV), SIVsm804E, which induces neuroAIDS in a high proportion of rhesus macaques and identified enhanced antagonism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…Direct infection of microglia/macrophages is thus perhaps responsible for the apoptotic changes and dysfunction/lack of activation in the presence of overwhelmingly high CSF VLs. This is further confirmed by the presence of SIV RNA in the brain tissues of our animals and by its colocalization with microglial nodules (11,24,25). Interestingly, in one of the animals that died in the early stages of the disease (SIV#2), SIV RNA staining seemed similar in shape to microglial cells (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Direct infection of microglia/macrophages is thus perhaps responsible for the apoptotic changes and dysfunction/lack of activation in the presence of overwhelmingly high CSF VLs. This is further confirmed by the presence of SIV RNA in the brain tissues of our animals and by its colocalization with microglial nodules (11,24,25). Interestingly, in one of the animals that died in the early stages of the disease (SIV#2), SIV RNA staining seemed similar in shape to microglial cells (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Using an immunofluorescence assay (IFA) coupled with both DNA and RNAscope, we see that RMs with SIVE harbor SIV DNA that is transcriptionally active in Br-M⌽s within lymphoid-rich lesions. We have previously shown that CL757 is highly adapted to replicate in the CNS compared to its parental clone, SIVsmmE543-3 (E543-3), which is generally excluded from replicating in the CNS (22). Our study shows that while trafficking does occur between the CNS and the periphery, Br-mCD4s appear to harbor replication-competent virus in the CNS in the absence of SIVE.…”
Section: Discussionmentioning
confidence: 55%
“…The animals used in this study were taken from a variety of different studies as they became available. This included a subset of the animals inoculated with the neurotropic clone CL757, described previously (22). In a study by Matsuda et al 22, 8 animals were inoculated with CL757, and only 4 animals developed neuroAIDS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also evaluated whole-brain cell suspensions obtained from a separate group of SIV-infected monkeys (group B, n = 13), of which only six animals showed neurological symptoms and were found to have neuropathology consistent with SIVE, as described earlier (16).…”
Section: Methodsmentioning
confidence: 99%